Sijunzi decoction granules for the treatment of advanced refractory colorectal cancer: study protocol for a multicenter, randomized, double-blind, placebo-controlled trial - Nie, Shuchang; Su, Yingyu; Lu, Lu; Jing, Yanhua; Jiang, Zenghua; Xu, Yangxian; Wu, Tingting; Zhong, Yi; Wu, Hao; Chen, Junming; Ruan, Ming; Zheng, Lan; et al. (Frontiers in Medicine, 2025)
BackgroundColorectal cancer (CRC) ranks among the most common gastrointestinal cancers globally, with both its incidence and mortality rates showing an upward trend. In particular, the 5-year survival rate for stage IV CRC patients is only 14%. Conventional treatments such as chemotherapy and immunotherapy can lead to drug resistance, exacerbate gastrointestinal function damage, and induce immunosuppression. Sijunzi decoction (SJZD), as a fundamental formula of Traditional Chinese medicine (TCM), has been demonstrated to confer distinct advantages in treatment of CRC. Therefore, we designed this trial to explore the efficacy of SJZD for the treatment of advanced refractory CRC.MethodsA multicenter, randomized, double-blind, placebo-controlled trial is being conducted to assess the effectiveness of SJZD combined with standard therapy for treating advanced refractory CRC. Patients with advanced CRC will be recruited and randomly allocated to either the SJZD treatment group or the placebo group in a 1:1 ratio. Both groups will receive standard treatment. The intervention period will last for 6 months, with follow-up assessments every 8 to 10 weeks. Progression-free survival (PFS) is the main outcome measure. And the secondary outcomes contain duration of disease control (DDC), overall survival (OS), completion rate of chemotherapy, incidence of treatment-related adverse events, quality of survival scale score for tumor patients and changes in spleen deficiency patient-reported outcome (PRO) scores following the intervention.Expected outcomesTo the best of our knowledge, this trial marks the first clinical investigation into the therapeutic potential of SJZD for managing advanced refractory CRC. The primary aim of this study is to provide robust clinical evidence to support the integration of TCM with Western medicine in the treatment of advanced refractory CRC.Trial registrationThe trial was registered at Chinese Clinical Trial Registry, http://www.chictr.org.cn (Registration No: ChiCTR2200065434); Date: 2022-11-04.